1992
DOI: 10.1002/sia.740190187
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged lifetime of electrochromism of amorphous WO3–TiO2 thin films

Abstract: The lifetime of the electrochromism of the W0,-TiO, films prepared by vacuum evaporation is found to exceed that of WO, films by a factor of five. X-ray difiactioo has revealed that the crystal structure of W0,-TiO, films stays amorphous, while crystalline compounds are formed in amorphous WO, films after colouring and bleaching. W0,-TiO, films stay amorphous after they are annealed at 40O0C, although WO, films crystallize. SIMS and XPS analyses have revealed that half the amount of lithium injected during a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 12 publications
(2 reference statements)
2
35
0
Order By: Relevance
“…It should be inferred that mixed anatase (and even rutile) titania and tungstenia form intermolecular solid oxide solutions of a rather high altervalent capacity, compatible both in amorphous and crystalline forms of the corner sharing WO 6 and edge sharing TiO 6 octahedrons, with pronouncedly increased electrochromic features even at rather high contents of the former [41,42]. In fact, highly charged W 6+ cations favor the reversible acid dissociation of water molecules and thereby such electrochromic layers exhibit well-defined ion exchange and electron conductive properties [23].…”
Section: Potentiodynamic Evidence For the Primary Oxide Spillover Phementioning
confidence: 99%
“…It should be inferred that mixed anatase (and even rutile) titania and tungstenia form intermolecular solid oxide solutions of a rather high altervalent capacity, compatible both in amorphous and crystalline forms of the corner sharing WO 6 and edge sharing TiO 6 octahedrons, with pronouncedly increased electrochromic features even at rather high contents of the former [41,42]. In fact, highly charged W 6+ cations favor the reversible acid dissociation of water molecules and thereby such electrochromic layers exhibit well-defined ion exchange and electron conductive properties [23].…”
Section: Potentiodynamic Evidence For the Primary Oxide Spillover Phementioning
confidence: 99%
“…Several authors have shown that reversibility can be improved by adding TiO to the tungsten oxide. The lifetime of WO -TiO thin films can be five times longer than that of pure WO (10,11). Therefore several studies have been undertaken to obtain more information on the structure and electrochemical properties of WO -TiO thin films (12).…”
Section: Introductionmentioning
confidence: 99%
“…Mixed anatase (and even rutile) titania, and in particular tungstenia, niobia and tantalia form intermolecular solid oxide solutions of a high altervalent capacity, compatible both in amorphous and crystalline forms of the edge sharing TiO6 and the corner sharing WO6 octahedrons, with pronouncedly increased electrochromic features even at high contents of the former. [49,50] In fact, highly charged W 6+ cations, like Nb 5+ , additionally favor the spontaneous reversible adsorptive dissociation of water molecules, [12,13] and thereby such electrochromic layers exhibit well defined ion exchange and electron conductive properties. [18−20] Thus, one of the fundamental contributions of the present paper is to show that prevailing anatase titania in the form of a composite mixed valence catalytic hypo-d-(f)-oxide support with tungstenia (and/or even more so niobia, tantalia and molybdenia), behaves in a compatible way and regarding the (Pt/H0.35WO3 ⇔ Pt/W(OH)6) bronze type equilibrium, so that the consequent reversibility features, the same properties as pure tungsten bronze itself, all of them have even further advanced by hypo-f-oxide ingredients (Ce,Gd,Ho,La, etc.)!…”
Section: Striping Voltammetry Evidence For the Primary Oxide Latent Smentioning
confidence: 99%